2022
DOI: 10.1007/s00420-022-01901-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between telework from home and the psychosocial work environment: a systematic review

Abstract: Objective Telework from home (TWFH) has become routine for many, yet research on how this may affect the psychosocial work environment is sparse. To understand the effects that TWFH may have on the psychosocial work environment, this systematic literature review identified, evaluated, and summarized findings on the association of TWFH with factors of the psychosocial work environment. Methods Searches were conducted in MEDLINE, Embase, Amed, PsycINFO, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 74 publications
0
5
0
3
Order By: Relevance
“…We found that access to TWFH moderated the relationship between office design and sickness absence, although not as expected; access to TWFH amplified, rather than attenuated, differences between private and conventional open-plan offices. Previous studies have indicated that effects of flexible work arrangements depend on whether the arrangement is perceived as voluntary ( 29 , 39 ). One explanation for our finding could be that employees in private and open-plan offices differ in perceptions of freedom of choice in teleworking from home as a function of the office environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that access to TWFH moderated the relationship between office design and sickness absence, although not as expected; access to TWFH amplified, rather than attenuated, differences between private and conventional open-plan offices. Previous studies have indicated that effects of flexible work arrangements depend on whether the arrangement is perceived as voluntary ( 29 , 39 ). One explanation for our finding could be that employees in private and open-plan offices differ in perceptions of freedom of choice in teleworking from home as a function of the office environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have indicated that TWFH increases presenteeism (ie, working while ill) ( 27 ), which could result in an apparent decrease in sickness absence in the short-term, access to TWFH might protect against sickness absence through other mechanisms. As a form of time-spatial flexibility ( 28 ), access to TWFH may reduce sickness absence through increased decision latitude and job autonomy ( 29 ), which are among the strongest and most consistent predictors of outcomes such as sickness absence and disability retirement ( 30 , 31 ). In a similar vein, access to TWFH might buffer some of the negative aspects that pervade shared-room and open-plan offices (eg, distractions, lack of privacy, crowding) by providing ways to regulate input and output privacy ( 32 ) or by reducing time spent coping with environmental stressors ( 33 ).…”
mentioning
confidence: 99%
“…Die für das Homeoffice charakteristische Belastungssituation erweist sich bei den Befragten in "Unternehmensorganisation, Buchhaltung, Recht und Verwaltung" als vielschichtig beziehungsweise ambivalent. Gleiches berichten nicht nur die oben genannten Studien aus dem deutschsprachigen Raum, sondern auch die internationale Literatur (Berling et al 2022;Ipsen et al 2021;Vleeshouwers et al 2022;Koren et al 2023). Auf der einen Seite sind größere zeitliche Spielräume und Einflussmöglichkeiten bei geringeren emotionalen Belastungen festzustellen, während auf der anderen Seite eine vermehrte Entgrenzung sowie schwierigere Vereinbarkeit von Arbeit und Privatleben bei höheren quantitativen Anforderungen berichtet wird.…”
Section: Diskussionunclassified
“…A systematic review by Hackney et al (2022) reports mixed support for working from home on employee productivity across k = 37 reviewed studies, with observed linear relations being either negative, null, or positive across these studies. Similarly, a systematic review by Vleeshouwers et al (2022) concluded that there was mixed evidence for relations between working from home and aspects of the psychosocial work environment (e.g., professional isolation; job satisfaction; k = 43). For example, research has found inconsistent linear relations between working from home and job satisfaction, with some studies suggesting positive and some null relations.…”
Section: Recent Research On Working From Homementioning
confidence: 99%
“…For example, research has found inconsistent linear relations between working from home and job satisfaction, with some studies suggesting positive and some null relations. Vleeshouwers et al (2022) concluded that there was a pressing need for higher-quality research on working from home to address these questions, including the need for research to consider multi-wave longitudinal designs, include precise measures of time use and location of work, and to use validated measures -each of which we address in the present study.…”
Section: Recent Research On Working From Homementioning
confidence: 99%